Mini-implant Usage in Orthodontic Practice - (:unkn) unknown (AVES PRESS LTD, 2015)
Objective: The present study was designed to investigate the general anchorage protocols and especially the tendencies during mini-implant usage among Turkish orthodontists. The main aim of the survey is to reveal if mini-implants are being used more than once and in different patients. Materials and Method: This is a cross-sectional study conducted with orthodontists who are members of the Turkish Orthodontic Society. The orthodontists were asked to click on a link to complete an automated questionnaire of 27 multiple-choice questions. Results: It was found that mini-implants are used by a great majority of the participants and in various cases. General tendencies during mini-implant usage show compatibility with the literature. Conclusion: This survey displays the preferences of Turkish orthodontists regarding mini-implant usage in their clinical practice. Moreover, it is especially important for documenting the fact that mini-implants are being used more than once and also in different patients.
Keywords: Mini-implant reusage; Miniscrew; Orthodontic mini-implants; Survey